Comparison of the Effectiveness of Pill Boxes and Medication Charts in Improving Medication Adherence Among Elderly Patients in Social Service Centers - Shalahuddin Al Madury; Arina Titami; Dwi Resky Mulyono; Ahmad Suyudi Rustam (Indonesian Journal of Global Health Research, 2026)
Medication errors (ME) are medication-related problems that are the most common safety incidents in the elderly, one of themis about medication adherence. One intervention that can be provided to improve adherence is by using a medication reminder chart, or pill box, starting with education on the importance of medication adherence and training on how to use the pill box/medication chart by involving social care providers who can later play a role in assisting the elderly if there are obstacles in the future. The purpose of this study was to compare the effectiveness of pill boxes and medication charts in improving medication adherence in elderly patients at social service centers in Yogyakarta. This research will be conducted with a quasi-experimental study design; with a two-group pretest-posttest research design. This research was conducted from July to September 2025 at two Social Service Centers in Yogyakarta. Sampling using a purposive sampling technique involving 30 clients in each group, data collection prospectively on elderly subjects, undergoing chronic disease treatment. The level of adherence is measured by interviews using the Morisky Medication Adherence Scale (MMAS-8) questionnaire. Validity and reliability test of the Indonesian version of the MMAS-8 Questionnaire, which has been tested for validity and reliability by previous researchers, with a convergent validity value of r = 0.883, and the Cronbach's alpha coefficient reliability result was 0.824. The characteristics of the clients in this study were mostly female, pre-elderly, had basic education, no comorbidities, duration of drug use <5 years, received drugs from polyclinics, and the type of therapy was >1 type of drug. There was a significant effect between the pill box and medication chart groups in increasing client adherence with a P value of 0.033. There was no significant effect in changes in the level of adherence between the two groups (P-value 0.232), and there was a positive change in the increase in the average value of client adherence scores. A significant difference was observed between the pill box and medication chart groups in improving medication adherence.